2019
DOI: 10.1038/s41598-019-38503-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125a enhances self-renewal, lifespan, and migration of murine hematopoietic stem and progenitor cell clones

Abstract: Expansion of hematopoietic stem cells (HSCs) is a ‘holy grail’ of regenerative medicine, as successful stem cell transplantations depend on the number and quality of infused HSCs. Although many attempts have been pursued to either chemically or genetically increase HSC numbers, neither clonal analysis of these expanded cells nor their ability to support mature blood lineages has been demonstrated. Here we show that miR-125a, at the single cell level, can expand murine long-term repopulating HSCs. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Especially of interest is the microRNA cluster containing miR-99b, let-7e, and miR-125a that was higher enriched in the aEVs and within the Top50 most abundant miRNAs. miR-125a controls the size of the stem cell population by regulating hematopoietic stem/progenitor cell apoptosis (Guo et al, 2010;Wojtowicz et al, 2019). Although downregulation of proapoptotic genes were not identified in the RNAseq analyses of UCB-CD34 + cells in response to aEVs and fEVs, inhibition of apoptosis could take place at later stage or only present in subset of expanding UCB-CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially of interest is the microRNA cluster containing miR-99b, let-7e, and miR-125a that was higher enriched in the aEVs and within the Top50 most abundant miRNAs. miR-125a controls the size of the stem cell population by regulating hematopoietic stem/progenitor cell apoptosis (Guo et al, 2010;Wojtowicz et al, 2019). Although downregulation of proapoptotic genes were not identified in the RNAseq analyses of UCB-CD34 + cells in response to aEVs and fEVs, inhibition of apoptosis could take place at later stage or only present in subset of expanding UCB-CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although downregulation of proapoptotic genes were not identified in the RNAseq analyses of UCB-CD34 + cells in response to aEVs and fEVs, inhibition of apoptosis could take place at later stage or only present in subset of expanding UCB-CD34 + cells. In more recent work by Wojtowicz et al (2019), miR-125a was identified to expand murine long-term repopulating hematopoietic stem cells and increase the number of hematopoietic stem cells in vivo. In addition, similar to the study of Xie et al, we identified miR-21 that has been reported to be involved in hematopoiesis (Bhagat et al, 2013;Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are endogenous small non-coding RNAs that are completely or incompletely complementary to the 3′-UTR of the target gene to regulate gene expression 4 . An increasing number of researches have indicated that microRNAs might participate in hematopoiesis 5 7 . Furthermore, microRNAs have been demonstrated to be promising diagnostic and prognostic biomarkers and are considered as therapeutic molecular targets in MDS 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, studies from multiple laboratories have convincingly demonstrated the unique ability of miR-125 to regulate HSCs [1,3,5,7,8]. On ectopic overexpression of miR-125a, the self-renewal capacity of HSCs is increased in both murine and human cells [8]. Remarkably, mir-125a is also able to confer on committed progenitors long-term repopulating ability, which they normally lack [7].…”
mentioning
confidence: 99%
“…Remarkably, mir-125a is also able to confer on committed progenitors long-term repopulating ability, which they normally lack [7]. Using cellular barcoding, we recently found that mir125a is able to extend the longevity of HSC clones [8].…”
mentioning
confidence: 99%